EFEKTIVITAS BANGUNAN PANTAI UNTUK PENANGGULANGAN ABRASI DI KABUPATEN PADANG PARIAMAN - aulya, aulya rahmadani; Rahmanelli, Rahmanelli (JURNAL BUANA, 2023)
This study is intended to achieve: (1) Changes in coastline and sedimentation distribution in 2003, 2013 and 2023, (2) Changes in land cover in 2003, 2013 and 2023, (3) The effectiveness of coastal buildings for abrasion mitigation in Padang Pariaman Regency. This type of research uses quantitative moteode with a spatial approach. The data used were landsat 5 TM and landsat 8 OLI/TIRS images, using Digital Shoreline Analysis System (DSAS) techniques, Total Suspended Solid (TSS) distribution, and Supervised Classification. (1) Changes in coastline in 2003-2023 NSM accretion is 84.18 meters and NSM abrasion -54.16 meters, EPR accretion 2.9 meters/year and EPR abrasion -2.1 meters/year, Abrasion occurs in Nagari Ketaping, Ulakan and Pilubang. The results of the Jaelani algorithm in 2003-2023 are 0.86 - 1.05 mg / l, the deposition distribution area is 4268.92 Ha - 16609.9 Ha. (2) Land cover change 2003-2023, buildings from 13% - 25%, forests from 32.2% - 30.2%, agriculture/plantations from 42.6% - 24.5% and water bodies 12% - 19%. (3) the results of Satelite Imagery there are 9 Jetties and 8 Groins, the effectiveness of abrasion countermeasures based on the length of the coastline, sedimentation distribution and land cover conditions per Nagari / segment, namely there are 14 Jetties and 278, Groin I and T types are effective in overcoming abrasion.